Determinants of Employee Performance Transformation in Islamic Banking: Evidence from Palu, Indonesia - Abdul Jalil; Rizki Amalia; Taufik Ridha (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Organizational transformation in Islamic banking has been widely discussed; however, how internal socio-technical structures and leadership mechanisms jointly influence employee performance transformation still requires more empirical evidence, particularly in regional contexts. Addressing this gap, this study examined the direct and moderating effects of information technology, organizational commitment, organizational culture, reward systems, and leadership on employee performance transformation in Islamic banks in Palu City, Indonesia. A quantitative survey design was employed involving 155 employees from five Islamic bank branches, including one main branch and four sub-branches. Primary data were collected using structured, closed-ended questionnaires administered face-to-face. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS. The findings revealed that information technology, organizational commitment, organizational culture, reward systems, and leadership each had a positive and significant direct effect on employee performance transformation. Leadership demonstrated a selective moderating role by strengthening the relationships between information technology and performance and between reward systems and performance. However, leadership did not significantly moderate relationships involving organizational commitment or organizational culture, indicating the dominance of motivation and embedded Islamic values. The study contributes to socio-technical and leadership literature by showing leadership functions as an enabling factor, with practical implications for ethical digital banking.